2020
DOI: 10.1038/s41598-020-71845-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anxiety and dual-task on upper limb motor control of chronic stroke survivors

Abstract: This study was designed to investigate the effects of anxiety and dual-task on reach and grasp motor control in chronic stroke survivors compared with age- and sex-matched healthy subjects (HC). Reach and grasp kinematic data of 68 participants (high-anxiety stroke (HA-stroke), n = 17; low-anxiety stroke (LA-stroke), n = 17; low-anxiety HC, n = 17; and high-anxiety HC, n = 17) were recorded under single- and dual-task conditions. Inefficient reach and grasp of stroke participants, especially HA-stroke were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, when considering motor control rather than gaze a study using 100 older adults found that a group with high task-specific anxiety of falling demonstrated a higher stride length, a higher stride time variability and lower gait velocity compared to those with a low task-specific anxiety of falling [29]. Furthermore, stroke patients with high generalised anxiety showed distinctly different reach-and-grasp movements compared to those with low generalised anxiety (longer normalised movement time, lower and earlier peak velocity and delayed hand opening) [30]. This collection of studies, with many more not reported here, demonstrate a clear relationship between anxiety levels and characteristic of gaze behaviour and movement behaviour in older adults.…”
Section: The Influence Of Anxiety On Movementmentioning
confidence: 99%
“…Furthermore, when considering motor control rather than gaze a study using 100 older adults found that a group with high task-specific anxiety of falling demonstrated a higher stride length, a higher stride time variability and lower gait velocity compared to those with a low task-specific anxiety of falling [29]. Furthermore, stroke patients with high generalised anxiety showed distinctly different reach-and-grasp movements compared to those with low generalised anxiety (longer normalised movement time, lower and earlier peak velocity and delayed hand opening) [30]. This collection of studies, with many more not reported here, demonstrate a clear relationship between anxiety levels and characteristic of gaze behaviour and movement behaviour in older adults.…”
Section: The Influence Of Anxiety On Movementmentioning
confidence: 99%
“…One explanation for this could be that real-world hand tasks such as carrying a cup of water to the table or pouring laundry detergent into the washer increase the motor and attentional demands of the task. The literature on dual tasks demonstrates that increased motor and cognitive demands decrease UE performance time and motor control in individuals with stroke compared to healthy populations [ 46 , 47 ], so it is not surprising that tasks completed at home with increased hazards and decreased safety would be a deterrent to use the affected side.…”
Section: Discussionmentioning
confidence: 99%
“…Under the effect of such drivers, we cannot exclude that motor performance might increase, comparing to our protocol including reaching movements at natural speed. It was also demonstrated with kinematic assessment that performing a well-learned upper limb movement with concurrent cognitive task leads to decreased efficiency of motor control in chronic stroke survivors ( 39 ).…”
Section: Discussionmentioning
confidence: 99%